Improving Reading Comprehension Ability of the Eleventh Grade Students of MAN 5 Jombang through Jigsaw Technique - SEPTIAN RAGIL ANANDITA (Universitas KH. A. Wahab Hasbullah, 2020)
This study was conducted to improve the student’s reading comprehension ability on narrative text through Jigsaw technique. The study was classroom action research; the subject was students from eleventh grade of IPS 3 (Social Science). It was chosen because this class got the lowest result of daily test on reading skill, which was used as preliminary study. The average score on preliminary test was 61.2 and only 40% students got passed the standard minimum of achievement (KKM). The minimal completeness criterion was 75. The cycle was held to increase the students’ achievement. First, the teacher made the colorful paragraph of text to make the students more interested in the reading comprehension ability. The second, the teacher motivated the students to be more active in discussion then asking them not was shy or afraid to ask question or give opinion. The teacher also motivated to the group leader to be able to control the optimal group discussion. The third, the teacher also arranged the balance of slow leaner and high leaner composition in each group. It was hope the high learner could help the slow learner. And at the end of cycle was evaluated. The result of posttest in cycle 2 was: the average score of the students test were increased from 72.2 in cycle I became 80.4 in posttest cycle II. The students who gained the standard minimum of achievement increased from 65% in cycle I became 80% in posttest cycle II. It showed that the low achievement had improved.